Antioxidant Enzyme Activities of some Brassica Species - Rodica SOARE; Maria DINU; Cristina BĂBEANU; Mihaela POPESCU (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture, 2017)
This paper set out to comparatively study five species: white cabbage (Brassica oleracea L. var. capitata alba Alef.), red cabbage (Brassica oleracea L. var. capitata f. rubra Alef.), Kale (Brassica oleracea L. var. Acephala), cauliflower (Brassica oleracea var. botrytis) and broccoli (Brassica oleracea var. cymosa) in order to identify those with high enzymatic and antioxidant activities. The enzymatic activity of superoxide dismutase (SOD), catalase (CAT) and soluble peroxidase (POX) as well as the antioxidant activity against 2.2’-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid (ABTS) radical cation were determined. Total superoxide dismutase activity was measured spectrophotometrically based on inhibition in the photochemical reduction of nitroblue tetrazolium. Total soluble peroxidase was assayed by measuring the increase in A436 due to the guaiacol oxidation and the catalase activity was assayed through the colorimetric method. The capacity of extracts to scavenge the ABTS radical cation was assessed colorimetric using Trolox as a standard. The obtained results show that studied enzymatic activities and the antioxidant activity against ABTS vary depending on the analyzed species. So, among the studied Brassicaceae species, it emphasize red cabbage with the highest enzymatic activity (CAT 22.54 mM H2O2/min/g and POX 187.2 mM ΔA/1min/1g f.w.) and kale with highest antioxidant activity, of 767 μmol TE/100g f.w. The results of this study recommendintroducing the studied varieties in diet due to the rich antioxidant properties.